Design and Build a Spare Parts Management System in the Instrumentation and Climatology Equipment Engineering Sub-Sector - Sefnath Erens Korwa; Sri Poedji Lestari; Bernadus Gunawan Sudarsono (Yayasan Bina Internusa Mabarindo, 2022)
The BMKG's Instrumentation and Climatology Equipment Engineering Sub Division has one of the tasks of preparing and providing spare parts for climatological equipment. The management of these spare parts is to meet the demand for replacement of climatological equipment spare parts in all regional task-implementing units including the AWS, AAWS and ARG spare parts. In managing spare parts for climatological equipment, there are several obstacles, including the absence of a system that helps in the spare parts management process . Errors in managing spare parts data often occur . The number of spare parts is increasing but the number of staff is limited, making handover minutes is still slow. and not yet computerized properly. There is no database system that can assist staff in managing, monitoring and making reports on the handover of climatology equipment . The purpose of this research is to design and create an information system for managing spare parts in the Instrumentation and Climatology Equipment Engineering Sub-Sector. From the analysis of the current system, there are four processes: incoming spare parts, demand for spare parts and outgoing spare parts and updating of spare parts stock. In the business process, the proposed input data is replaced with an incoming spare parts for, a spare parts request form, an outgoing spare parts form, but the spare parts stock update is omitted because the data has been updated automatically. The results of this study are to create an application of spare parts management information systems in the Instrumentation and Climatology Equipment Engineering Sub-Sector using the PHP programming language and stored in the mysql database so that it can produce real-time spare parts management, can monitor the availability of spare parts, present statistical data spare parts, and can produce minutes of the handover of climatological equipment spare parts.